A sociological study to explore the knowledge of Pre-Exposure Prophylaxis at Rhodes University - Ntshinga, Throny (Rhodes University, Faculty of Humanities, Department of Sociology, 2019)
South Africa has a very high prevalence rate of HIV infections, this is why this exploratory qualitative study examines the Rhodes University's HIV policy and its awareness programmes, with a specific focus on Pre-Exposure Prophylaxis (PrEP). The World Health Organisation's (2016-2017) recommendations for Pre-exposure Prophylaxis has been accepted and rolled-out nationwide by the South African Department of Health. This is to maintain the HIV-negative status of not only the general public, but specifically students at higher institutions of learning. PrEP has been integrated with other HIV prevention methods through the Higher Education and Training HIV/AIDS programme. Semi-structured in-depth interviews were conducted with five female and four male students, and six health care staff members at Rhodes University. Data was thematically analysed, and the findings show that there is a lack of knowledge of both the HIV policy and Pre-Exposure Prophylaxis among the participating students. However, the staff members are knowledgeable due to the fact that they work in health care.
Keywords: Pre-exposure prophylaxis -- South Africa; HIV infections -- Prevention -- South Africa; AIDS (Disease) -- Prevention -- South Africa; AIDS (Disease) -- Government policy -- South Africa; AIDS (Disease) -- Study and teaching -- South Africa; Health education (Higher) -- South Africa; Rhodes University -- Students -- Health and hygiene